Criminal Law Enforcement of Consumer Rights of Victims of Dangerous Cosmetics in Pekanbaru Based on Law No. 8 of 1999 - Ernawaty, Beby; Harahap, Irawan; Pardede, Rudi (Raudhah Publisher, 2024)
The enforcement of criminal law on consumer rights for victims of hazardous cosmetics in the jurisdiction of the Riau Police, particularly in Pekanbaru City, under Law Number 8 of 1999 on Consumer Protection, faces significant challenges. Article 4 of the Consumer Protection Law grants consumers the right to comfort, security, and safety in using products, along with accurate, clear, and honest information. However, hazardous cosmetics containing substances like mercury and hydroquinone continue to circulate freely, both in physical stores and online, indicating that law enforcement intended to protect consumers remains inadequate. Using a sociological legal approach, this research reveals a gap between the law and its implementation, as unsafe cosmetics are widely available, contradicting consumer rights as defined in the Consumer Protection Law. Key obstacles include low public awareness and participation, as many victims fail to report cases; limited inter-agency coordination, particularly with the Food and Drug Supervisory Agency (BPOM); and restricted access to data on the distribution and sale of dangerous cosmetics, especially those sold online. To address these enforcement challenges, it is necessary to improve institutional coordination, create an online complaint platform for consumers to report cases directly and anonymously, strengthen legal evidence and investigative depth in cases involving hazardous cosmetics, and conduct regular market surveillance to prevent the distribution of illegal and harmful products. These measures are essential to bridging the gap between the legal framework and practical enforcement, ultimately ensuring better consumer protection against the risks posed by hazardous cosmetics.